Werewolf, There Wolf: Variants in Hairless Associated with Hypotrichia and Roaning in the Lykoi Cat Breed. - Buckley RM; Gandolfi B; Creighton EK; Pyne CA; Bouhan DM; LeRoy ML; Senter DA; Gobble JR; Abitbol M; Lyons LA; 99 Lives Consortium (MDPI (Basel, Switzerland), 2020)
A variety of cat breeds have been developed via novelty selection on aesthetic, dermatological traits, such as coat colors and fur types. A recently developed breed, the lykoi (a.k.a. werewolf cat), was bred from cats with a sparse hair coat with roaning, implying full color and all white hairs. The lykoi phenotype is a form of hypotrichia, presenting as a significant reduction in the average numbers of follicles per hair follicle group as compared to domestic shorthair cats, a mild to severe perifollicular to mural lymphocytic infiltration in 77% of observed hair follicle groups, and the follicles are often miniaturized, dilated, and dysplastic. Whole genome sequencing was conducted on a single lykoi cat that was a cross between two independently ascertained lineages. Comparison to the 99 Lives dataset of 194 non-lykoi cats suggested two variants in the cat homolog for Hairless (HR) (HR lysine demethylase and nuclear receptor corepressor) as candidate causal gene variants. The lykoi cat was a compound heterozygote for two loss of function variants in HR, an exon 3 c.1255_1256dupGT (chrB1:36040783), which should produce a stop codon at amino acid 420 (p.Gln420Serfs*100) and, an exon 18 c.3389insGACA (chrB1:36051555), which should produce a stop codon at amino acid position 1130 (p.Ser1130Argfs*29). Ascertainment of 14 additional cats from founder lineages from Canada, France and different areas of the USA identified four additional loss of function HR variants likely causing the highly similar phenotypic hair coat across the diverse cats. The novel variants in HR for cat hypotrichia can now be established between minor differences in the phenotypic presentations.
Keywords: Felis catus; HR; atrichia; domestic cat; fur; naked; Alleles; Animals; Breeding; Cats; Hair; Hair Color; Hair Follicle; Polymorphism, Single Nucleotide